Ethnic composition of repressed in Donbas during 1941-1982 years - Balykin, Ivan (Skhid, 2014)
The article deals with the quantitative composition of victims of repression in Donetsk and Lugansk regions, highlights the main features of the periods of repressions during the 1941-1982 years, called tendencies in sentences, distinguishes most numerous nationalities that have been repressed. We study the ethnic composition of the repressed in the Donbas in 1941-1982 years. In the process of implementing the policy of repressions in Donbas as in Ukrainian SSR as well periods of increase and decrease of intensity can be clearly seen. The most devastating wave of persecutions occurred in 1941-1945 and 1948-1953 years. The first was caused by the events of World War II, the second - by the fight against "rootless cosmopolitanism" and "wrecking". The policy of the governing party was similar to repressions. It was directed on the leveling of the peoples of the USSR and intention to create a new community of people - "Soviet people". The results of this are well illustrated by Donbas, where today a large proportion of the population does not speak adequately state language. Thus, author concludes that Ukrainians, Russians and Germans suffered the most from repression, Poles, Jews, Greeks, Bulgarians and Belarusians had also significant losses. In total nearly 40 nationalities represented in Donetsk and Lugansk regions were illegally repressed.